Pengaruh Jurusan, Biaya dan Kualitas terhadap Keputusan Siswa Untuk Masuk SMK Negeri 2 Batanghari - Ahmad Fithoni; Zazili Zazili (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
This study aims to determine the Effect of Department, Cost and Quality on Student Decisions to enter Kujuruan Middle School (SMK). This research is descriptive quantitative with the number of respondents as many as 110 people from students of SMK Negeri 2 Batanghari. The analysis used is multiple regression, partial test (t test), simultaneous test (f test), and determination test (R2). The results showed that the most dominant independent variable or a positive influence was the Cost variable (X2) with tcount (10,969)> t table (1,65936). For F Test it is known that Fcount = 101.212> Ftable = 2.69 This means that together the Department, Cost and Quality influence the Student's Decision to enter SMK Negeri 2 Batanghari because the calculated f value of 101.212 is greater than the f table 2.69 (101.212 > 2.69). While seen from the coefficient of determination. Department, Cost and Quality influence the Decision of Students to enter SMK Negeri 2 Batanghari by 73.4% and the remaining 2.66% is influenced by other factors not examined in this study.